Women$1 (Bs Empowerment and Intimate Partner Violence: Evidence from a Multidimensional Policy in Indias - Chatterjee, Somdeep; Poddar, Prashant (Economic Development and Cultural Change, 2024)
In this paper, we study a multidimensional women's empowerment program from India to estimate its effects on intimate partner violence faced by women. We exploit plausibly exogenous geographical variation in the implementation of the program and cohort-variation generated by eligibility rules to estimate our effects. Using a reduced form difference-in-differences design, we find evidence of lesser-reported emotional and physical violence for women potentially exposed to the program. Overall, women reported lesser intimate partner violence and controlling behavior on account of the empowerment intervention. We conjecture that improved anthropometric outcomes, higher literacy, and better labor market opportunities serve as potential mechanisms causing this effect.
Keywords: Higher Literacy; Intimate Partner Violence; Multidimensional Policy in India; Physical Violence; Women's Empowerment